2019
DOI: 10.1007/s00270-019-02300-y
|View full text |Cite
|
Sign up to set email alerts
|

Peri-tumoral Metallic Implants Reduce the Efficacy of Irreversible Electroporation for the Ablation of Colorectal Liver Metastases

Abstract: Purpose:To evaluate the effect of peri-tumoral metallic implants (MI) on the safety and efficacy of percutaneous irreversible electroporation (IRE) of colorectal liver metastasis (CRLM). Materials and Methods:In this retrospective study, 25 patients (12 women, 13 men; MI: 13, No MI: 12 ) were treated for 29 CRLM. Patient characteristics, tumor location and size, treatment parameters and the presence of MI were evaluated as determinants of local tumor progression (LTP) with the competing risks model (uni-and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Clinicians should be aware of the reduction in electric field strength as a consequence of a metal stent near the IRE electrodes. An increase in pulse number could potentially at least partially counteract the occurrence of an ineffective tumour ablation near a metal stent 14 . However, it is a delicate balance between an effective ablation and thermal effects or damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians should be aware of the reduction in electric field strength as a consequence of a metal stent near the IRE electrodes. An increase in pulse number could potentially at least partially counteract the occurrence of an ineffective tumour ablation near a metal stent 14 . However, it is a delicate balance between an effective ablation and thermal effects or damage.…”
Section: Discussionmentioning
confidence: 99%
“…In a case report, severe complications have been described after IRE treatment in the proximity of a metal stent, potentially caused by unintended thermal effects 13 . A retrospective clinical study demonstrated that IRE near small metal surgical clips (< 1 cm to tumour margin or needle electrodes) resulted in distortion of the electric field and inadequate coverage of the tumour, a less effective cell death and reduced treatment efficacy 14 . The presence of a metal clip was also significantly related to local tumour progression.…”
Section: Introductionmentioning
confidence: 99%
“…9,[15][16][17] Some reports describe percutaneous approach also for electrochemotherapy of cholangiocarcinoma, spine metastases 18,19 , lysis of portal vein thrombosis in hepatic hilum, and metastasis from renal cell cancer, however not in treatment of HCC. [20][21][22][23] In this report we therefore tested the feasibility, safety and effectiveness of electrochemotherapy with image guided percutaneous approach, in a patient with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The EP treatment is not associated with a change in the temperature of the exposed tissue, except for near the needles of the electrodes [5,6]; the treatment can be performed in "noble" structures, such as vessels and nerves, without risk of complication. Moreover, the collagen and vascular tissue structure do not undergo coagulative degeneration as observed with hyperthermic procedures, such as radiofrequency (RFA), microwave (MWA), high-intensity focused ultrasound (HIFU), and laser therapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage is the increased risk of damaging nearby non-target organs [7,8]. However, for irreversible electroporation, it was reported that the increase of pulse application could determine both an efficacy increase of the treatment and associated thermal damage [5,6], limited to the area around the electrodes [5,6,9]. This effect is minimized in cases of reversible electroporation, considering an electric protocol, according to European Standard Operating Procedures of Electrochemotherapy (ESOPE) [10][11][12], which consists of 8 pulses of 100 µs, divided into two groups of four, with inversion of the applied voltage, and an electric field of 1000 V/cm.…”
Section: Introductionmentioning
confidence: 99%